SiBCN-ZrO2 hybrid ceramic aerogels through the polymer-derived ceramics (PDCs) route - Liu, Hongli (2020)
The SiBCN-ZrO2 hybrid ceramic aerogels were fabricated by pyrolysis of preceramic aerogels prepared from Polyborosilane/Zirconium 5n-butoxide /Divinylbenzene (PSNB/ZBO/DVB) combining a simple hydrosilylation reaction with CO2 supercritical drying. The micromorphology and pore structure parameters of the preceramic hybrid aerogels were investigated. Structural evolution of the ceramic hybrid aerogels and the crystallization behavior were studied by scanning electron microscope (SEM), X-ray diffraction (XRD) and transmission electron microscopy (TEM). The results showed that all the preceramic hybrid aerogels had a typical mesoporous structure. The neck region between the particles of SiBCN-ZrO2 ceramic hybrid aerogels was gradually increased when the sintering temperatures increased from 750 °C to 1550 °C. After heat treatment at 1550 °C, the specific surface area and pore volume for the samples were drastically reduced down to 108.85 m2 g−1 and 0.49 cm3 g−1, respectively. The ZrO2 nanocrystals were well-distributed in amorphous SiBCN network backbone, the final crystalline phases were composed of hexagonal BN, β-SiC crystals and monoclinic ZrO2.